2019
DOI: 10.1002/cbin.11093
|View full text |Cite
|
Sign up to set email alerts
|

IL‐7 enhances the differentiation of adipose‐derived stem cells toward lymphatic endothelial cells through AKT signaling

Abstract: Our study was designed to investigate the effects of IL-7 during the differentiation process of adipose-derived stem cells (ADSCs) toward lymphatic endothelial cells (LECs). IL-7 was added to the traditional induced medium, which was called the IL-7 (þ) group, while the group that used traditional induced medium was called the IL-7 (À) group. After 7 days of induction of ADSCs, a comprehensive analysis was conducted between these two groups. We examined the changes in Prox1, LYVE-1, Podoplanin and VEGFR-3 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Endothelialization is a fundamental target for researchers and clinicians involved in vascular and valvular replacements ( 29 , 30 ). Varied modalities to differentiate and to promote ADSCs commitment toward ECs were described, including genomic manipulation ( 31 ), immune modulation ( 32 ), induced hypoxia ( 33 ), and specific growth factors ( 34 , 35 ). Comparative studies of differentiation of ADSCs toward ECs lineage revealed improved results when combinations of ECGS and shear were used ( 36 , 37 ) pointing to the importance of recreating the in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelialization is a fundamental target for researchers and clinicians involved in vascular and valvular replacements ( 29 , 30 ). Varied modalities to differentiate and to promote ADSCs commitment toward ECs were described, including genomic manipulation ( 31 ), immune modulation ( 32 ), induced hypoxia ( 33 ), and specific growth factors ( 34 , 35 ). Comparative studies of differentiation of ADSCs toward ECs lineage revealed improved results when combinations of ECGS and shear were used ( 36 , 37 ) pointing to the importance of recreating the in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They conducted an in vitro study using human ADSCs (5 × 10 5 cells) cultured by an induced medium with IL-7. They noticed an increase in RNA and protein levels of LEC markers (Prox-1, LYVE-1, podoplanin, and VEGF-3) in the ADSCs cultured with IL-7 and suggested that this cytokine enhances ADSC differentiation into LECs [19].…”
Section: I F F E R E N T I a T I O N P A R A C R I N E S E C R E T I O Nmentioning
confidence: 99%
“…Moreover, tube-like structures were formed by these differentiated ADSCs in the matrix gel [18]. Sun et al [19] aimed to investigate the effect of IL-7 on ADSC differentiation into LECs. They conducted an in vitro study using human ADSCs (5 × 10 5 cells) cultured by an induced medium with IL-7.…”
Section: I F F E R E N T I a T I O N P A R A C R I N E S E C R E T I O Nmentioning
confidence: 99%
“…In addition, ADSCs exhibit paracrine immunomodulatory and trophic effects in their local microenvironment. Emerging in vitro studies have investigated the possible mechanisms and benefit of ADSCs in the treatment of lymphedema, such as their capacity for differentiation into lymphatic endothelial cells (LECs)[ 16 , 17 ] and paracrine secretion of cytokines[ 18 ], chemokines[ 19 ] and exosomes[ 20 ], thereby promoting angiogenesis and modulating the immune response. Takeda et al[ 21 ] reported that, by secreting lymphangiogenic factors, ADSCs promote proliferation, migration, and tube formation of LECs in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Yen et al[ 23 ] showed that ADSCs promote lymphangiogenesis under stimulation of vascular endothelial growth factor-C (VEGF-C), a key lymphangiogenic factor, or in response to inhibition of TGF-β1; moreover, stimulation of ADSCs with VEGF-C was found to markedly increase cellular proliferation and cellular survival after in vivo implantation and to induce the expression of podoplanin, a lymphangiogenic cell marker. Sun et al[ 19 ] reported that interleukin-7 enhanced the differentiation of ADSCs into LECs via AKT signaling pathways. Most recently, Saijo et al[ 24 ] revealed that paracrine effects of ADSCs promoted lymphangiogenesis in irradiated LECs.…”
Section: Introductionmentioning
confidence: 99%